Housing neighborhoods as an interaction of enclosure and disclosure - Mangut, Burak; Ozsoy, Fatma Ahsen (Emerald, 2019)
Purpose The purpose of this paper is to focus on the interaction of enclosure and disclosure, and analyze the dynamics of this bond. It also investigates the interaction between open spaces and closed spaces in housing areas as fundamental public and private realms of the neighbourhoods to understand the relation between physical and social environments. Design/methodology/approach The research aims to grasp the effects of open spaces on the development of the physical and social structures in a community at the intersection of enclosure and disclosure. To display potentials of the relation between these two notions, the behavioural treatments at the intersection of open space and housing units as the basic modules of the pattern, and the effects of spatial organization forms on them are explored. The methodology of the study is formed through the clarification of tangible and intangible facts simultaneously, conducted by spatial and behavioural analysis. Findings The intersection of enclosure and disclosure in neighbourhoods receives both practical and academic attention. The zone not only creates appropriate conditions for a vital urban life, but also helps to generate social structure in the neighbourhood. Furthermore, although the modernist settlements are criticized because of urban monotony and lifelessness since the last two and three decades of the twentieth century, it is seen that the situations in which “the spatial organization of housing units” and “the formation of urban pattern of the settlement” were dealt synchronously generate vividness and achievement in an urban context. Originality/value The study aims to grasp how the intersection zone is affected by the differences of “urban activities in open spaces as one of the main indicators of vividness” and “spatial organization of dwelling units with a perspective from the other side of the border”. Moreover, to understand the capacity of the intersection zone in physical reality, the research aims to evaluate theoretical data through the actual dynamics of daily life. The combination of various research methods that constituted mostly spatial and behavioural analysis is one of the most robust sides of the research.